Interactive journalism : hackers, data, and code - Usher, Nikki (University of Illinois press, 2016)
"Traditional journalism faces the growing reality that the news business model remains an unsolvable problem. Audiences can go anywhere at any time. Technological and computing advances offer opportunities to explore on web and mobile beyond what has ever been possible before, thanks to an explosion in programming knowledge. The infrastructure and experience of information delivery has evolved to seemingly erase time and space boundaries. This larger setting for news, bound up in changes to economics, technology and culture, has created the conditions for a new subspecialty of the journalism profession to emerge: interactive journalism. In Interactive Journalism, Nikki Usher brings together a comprehensive theoretical and empirical portrait of this subspeciality. Beginning with a theoretical overview of professionalism, Usher provides a comprehensive history of fields that come together to define interactive journalism: computer assisted reporting, photojournalism and graphics. She then moves from the people behind interactive journalism to the work that these journalists do to the special abstract knowledge they provide the profession. With vignettes from across the world, she takes us from in-depth look at Al Jazeera English interactive creation to the BBC to the Guardian's data desk to the New York Times. Interactive Journalism illuminates the professions, people, work and knowledge of a subspeciality that has emerged in the age of the rise of digital culture as a possible answer to the decline and fall of traditional journalism"--